Online Customer Reviews and Online Customer Ratings on Product Purchasing Decisions Skintific through Customer Trust - Sari, Rakhma; Kusmawati, Rengganis; Dedu, May; Agustina, Agustina (Indonesian Journal of Advanced Research, 2025)
The rapid growth of Indonesia’s cosmetics industry is influenced by increasing skincare awareness. This study examines the impact of Online Customer Review and Online Customer Rating on Purchasing Decision, with Consumer Trust as a mediating variable. Using a quantitative method, data were collected from 167 Instagram users who had purchased Skintific products. Analysis via Partial Least Square with SmartPLS 3.0 reveals that both Online Customer Review and Online Customer Rating significantly affect Purchasing Decision, directly and indirectly through Consumer Trust. Consumer Trust strengthens the relationship between review, rating, and purchase. These findings highlight the need for strong reputation management to foster trust and boost loyalty, ultimately enhancing sales in the cosmetics sector.